Controlled progressive innate immune stimulation regimen prevents the induction of sickness behavior in the open field test - Chen Q; Tarr AJ; Liu X; Wang Y; Reed NS; DeMarsh CP; Sheridan JF; Quan N (Dove Medical Press, 2013)
Qun Chen, Andrew J Tarr, Xiaoyu Liu, Yufen Wang, Nathaniel S Reed, Cameron P DeMarsh, John F Sheridan, Ning QuanDivision of Oral Biology, Institute for Behavioral Medicine Research, The Ohio State University, Columbus, OH, USAAbstract: Peripheral immune activation by bacterial mimics or live replicating pathogens is well known to induce central nervous system activation. Sickness behavior alterations are often associated with inflammation-induced increases in peripheral proinflammatory cytokines (eg, interleukin [IL]-1β and IL-6). However, most researchers have used acute high dose endotoxin/bacterial challenges to observe these outcomes. Using this methodology may pose inherent risks in the translational interpretation of the experimental data in these studies. Studies using Escherichia coli have yet to establish the full kinetics of repeated E. coli peripheral injections. Therefore, we sought to examine the effects of repeated low dose E. coli on sickness behavior and local peripheral inflammation in the open field test. Results from the current experiments showed a behavioral dose response, where increased amounts of E. coli resulted in correspondingly increased sickness behavior. Furthermore, animals that received a subthreshold dose (ie, one that did not cause sickness behavior) of E. coli 24 hours prior were able to withstand a larger dose of E. coli on the second day (a dose that would normally cause sickness behavior in mice without prior exposure) without inducing sickness behavior. In addition, animals that received escalating subthreshold doses of E. coli on days 1 and 2 behaviorally tolerated a dose of E. coli 25 times higher than what would normally cause sickness behavior if given acutely. Lastly, increased levels of E. coli caused increased IL-6 and IL-1β protein expression in the peritoneal cavity, and this increase was blocked by administering a subthreshold dose of E. coli 24 hours prior. These data show that progressive challenges with subthreshold levels of E. coli may obviate the induction of sickness behavior and proinflammatory cytokine expression.Keywords: open field, E. coli, sickness behavior, repeated administration